2003
DOI: 10.1590/s0037-86822003000500004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de marcadores para o vírus da hepatite B em contatos domiciliares no Estado do Amazonas

Abstract: The aim of our investigation was to evaluate, with a prevalence study, the modes of transmission of Hepatitis B virus (HBV), within infected subjects and their household contacts in the State of Amazon, western Brazilian Amazon. We studied 97 index cases and 258 household contacts. Out of the 258 household contacts of HBV, 51.6% had serological markers of a past infection, 12.0% signs of active infection, suggesting that the virus circulates within household members. The high prevalence among siblings (23.6%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
7
1
4
Order By: Relevance
“…In contrast to our results, a study by Brasil et al (2003) demonstrated that of the total population studied in the state of Amazônia, 24.6% reported exposure to endemic area and 15.5% had percutaneous exposure before infection with HBV.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, a study by Brasil et al (2003) demonstrated that of the total population studied in the state of Amazônia, 24.6% reported exposure to endemic area and 15.5% had percutaneous exposure before infection with HBV.…”
Section: Discussioncontrasting
confidence: 99%
“…Para candidatos a doação de sangue, o VHC foi encontrado em 2,1% na região Norte, 1% no Centro-Oeste, 1,2% no Nordeste, 1,4% no sudeste e 0,6% no sul 10 . Em Lábrea, AM, foi encontrada prevalência de 49,9% para anti-HBc 6 , em Recife 12% para antiHBc 3 , Santa Catarina 0,6% para HBsAg, 5,4% para anti-HBc e 0,3% de anti-VHC 14 e em São Paulo com 16% de Anti-HBc…”
Section: Discussionunclassified
“…A study carried out in São Paulo showed that convicts, individuals admitted to correctional facilities, injecting IDU and people tattooed with materials not properly sterilized contribute to the spread of Hepatitis B in our country (27) and another study carried out in Minas Gerais identified a relationship between HBV infection and the presence of tattoos (28) .…”
Section: Discussionmentioning
confidence: 90%